The Ideal Indonesia's Musyawarah: A Remedy for the ASEAN Way - Jeko Spastyono; Ichsan Malike; Bambang Wahyudi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Over half a century has passed, yet ASEAN is again caught between two battling giants. Utilizing a literature review approach, we delve into this issue by focusing on the ASEAN way, which is the machine of ASEAN. Contrary to skeptics' views, the consensus mechanism's negative effects stem more from the non-intervention principle, which limits its utility. However, the key to addressing this issue lies in utilizing agenda to better consensus mechanisms to create a non-interference minimalized forum. The key is that ASEAN member states are willing to fund thousands of forums to achieve consensus on various issues. Indonesia, the nominal leader that habitually hedges between great power and the owner of musyawarah and mufakat used by TAC, is the best actor to initiate this idea. Currently, when ASEAN states are divided and cannot convince, much less help each other, Indonesia's Musyawarah and Mufakat, which brings all voices, including the taboo ones, to the table, could be the key to creating a special forum where ASEAN member states become strategists to help other member but maintain the dignity and autonomy of the helped member. Ultimately, what is usually swept under the rug and hinders the consensus-building process can be minimized, and ASEAN can become a more effective organization